Profile of cases notified for viral hepatitis in a University Hospital in the State of Alagoas, Brazil (Research, Society and Development, 2022)
Objective: To describe the profile of reported cases of viral hepatitis (HV) in a university hospital in the State of Alagoas. Methodology: Documentary, descriptive and retrospective study, with a quantitative approach. The information contained in the Compulsory Notification Information System was selected for HV, between the years 2017 to 2021, notified at the University Hospital Professor Alberto Antunes (HUPAA). The research sample was the entire universe of notifications made by the cause CID10 B19, in the HUPAA, in the period from 2017 to 2021. The description of the epidemiological profile was carried out through descriptive statistics of the data, from the calculation of absolute and relative frequencies. Results: The investigated sample consisted of 544 notifications. It is noted that there was a predominance of infections in patients aged between 50 and 64 years. The male sex was more expressive. It was observed that chronic hepatitis is the main clinical form, with prevalence of the etiological agent HBV. There is expressiveness in the number of individuals who did not receive vaccines for hepatitis A and B. Conclusion: From 2017 to 2021, the distribution of notifications for HV fluctuated over the years between adults and the elderly. It is inferred that measures aimed at improving the quality of notifications are important to reduce data inconsistencies, as well as to minimize the impacts that incongruous fillings may cause.